2014
DOI: 10.1002/2014gl062071
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of hurricane forecasts to cumulus parameterizations in the HWRF model

Abstract: The Developmental Testbed Center used the Hurricane Weather Research and Forecasting (HWRF) system to test the sensitivity of tropical cyclone track and intensity forecasts to different convective schemes. A control configuration that employed the HWRF Simplified Arakawa Scheme (SAS) was compared with the Kain-Fritsch and Tiedtke schemes, as well as with a newer implementation of the SAS. A comprehensive test for Atlantic and Eastern North Pacific storms shows that the SAS scheme produces the best track for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 25 publications
0
48
2
Order By: Relevance
“…It is worth mentioning that there have been several studies on the representation of track and intensity of TCs using the high-resolution Hurricane Weather Research and Forecasting Model (HWRF) [Gopalakrishnan et al, 2012[Gopalakrishnan et al, , 2013Biswas et al, 2014;Zhang and Marks, 2015], including TC rapid intensification [Kieu et al, 2014;Chen and Gopalakrishnan, 2015]. Other factors related to the improvement of the representation of the intensity of TCs include: spatial resolution and initialization [Gopalakrishnan et al, 2012], the choice of physical parameterizations [Ma and Tan, 2009;Gopalakrishnan et al, 2012;Biswas et al, 2014], vertical diffusivity of both momentum and heat [Gopalakrishnan et al, 2013], and horizontal diffusion [Zhang and Marks, 2015].…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that there have been several studies on the representation of track and intensity of TCs using the high-resolution Hurricane Weather Research and Forecasting Model (HWRF) [Gopalakrishnan et al, 2012[Gopalakrishnan et al, , 2013Biswas et al, 2014;Zhang and Marks, 2015], including TC rapid intensification [Kieu et al, 2014;Chen and Gopalakrishnan, 2015]. Other factors related to the improvement of the representation of the intensity of TCs include: spatial resolution and initialization [Gopalakrishnan et al, 2012], the choice of physical parameterizations [Ma and Tan, 2009;Gopalakrishnan et al, 2012;Biswas et al, 2014], vertical diffusivity of both momentum and heat [Gopalakrishnan et al, 2013], and horizontal diffusion [Zhang and Marks, 2015].…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…Other factors related to the improvement of the representation of the intensity of TCs include: spatial resolution and initialization [Gopalakrishnan et al, 2012], the choice of physical parameterizations [Ma and Tan, 2009;Gopalakrishnan et al, 2012;Biswas et al, 2014], vertical diffusivity of both momentum and heat [Gopalakrishnan et al, 2013], and horizontal diffusion [Zhang and Marks, 2015].…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2016msmentioning
confidence: 99%
“…A control configuration adopting the HWRF Simplified Arakawa Scheme (SAS) was compared with the Kain-Fritsch and Tiedtke schemes, as well as with newer implementation of the SAS. Averaging over almost 250 cases, they showed that the SAS scheme produced the best track forecasts ( Figure 1 of [5]) till a lead time of 72-84 hours followed very closely by KainFritsch scheme.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [3][4][5][6] have explored the Weather Research and Forecasting (WRF) model predictive ability sensitivity to its different physical parameterizations, that is, to the effects of varying the computational horizontal and vertical resolutions and the number of domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation